US House Prices by Census Division: Persistence, Trends and Structural Breaks - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper uses fractional integration methods to examine persistence, trends and structural breaks in US house prices, more specifically the monthly Federal Housing Finance Agency (FHFA) House Price Index for Census Divisions, and the US as a whole over the period from January 1991 to August 2022. The full sample estimates imply that the order of integration of the series is above 1 in all cases, and is particularly high for the aggregate series. However, when the possibility of structural breaks is taken into account, segmented trends are detected; the subsample estimates of the fractional differencing parameter tend to be lower, with mean reversion occurring in a number of cases, and the time trend coefficient being at its highest in the last subsample, which in most cases starts around May 2020.
Keywords: C22; E30; 330; US house prices; fractional integration; persistence; trends; structural breaks